2019
DOI: 10.1186/s13018-019-1336-1
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasty with femoral osteotomy and modular prosthesis for proximal femoral deformity

Abstract: Background Severe anatomical abnormalities exist in proximal femoral deformities (PFDs). Total hip arthroplasty (THA) is associated with drawbacks such as high surgical complexity, long operation time, requirement for high surgical skills, high incidences of postoperative complications, and poor efficacy. Objective This study aimed to investigate the short-term efficacy of THA with femoral osteotomy and modular prosthesis implantation for femoral fixation and reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Metaphysis stability is not compromised by the DFSCP. The proximal sleeve of S-ROM with porous coating helps maintain metaphysis stability and prevent stem subsidence [10]. At perforation, the distal tip of the stem is impacted into medial cortical bone, providing axial stability.…”
Section: Managing Distal Stem Cortical Perforationmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaphysis stability is not compromised by the DFSCP. The proximal sleeve of S-ROM with porous coating helps maintain metaphysis stability and prevent stem subsidence [10]. At perforation, the distal tip of the stem is impacted into medial cortical bone, providing axial stability.…”
Section: Managing Distal Stem Cortical Perforationmentioning
confidence: 99%
“…At perforation, the distal tip of the stem is impacted into medial cortical bone, providing axial stability. The cylindrical stem of S-ROM connects distal and proximal femoral segments and works like an intramedullary nail [10,11]. In addition, the distal flutes and fins in the stem can provide rotation stability [12,13].…”
Section: Managing Distal Stem Cortical Perforationmentioning
confidence: 99%
“…The choice of osteotomy and internal fixation mainly depends on the degree of anatomical abnormalities [ 3 ]. Deng et al [ 6 ] described that in patients with femoral deformities without associated fractures, THA, precise osteotomy, and correct choice of prostheses were key factors for femoral reconstruction and fixation. Kim et al [ 23 ] reported that total hip arthroplasty with trochanteric ostectomy rendered favorable results for patients with deformity of the proximal femur.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, proximal femoral deformity in adults can be induced by a wide variety of primary diseases, including poliomyelitis sequela, proximal femoral fibrous dysplasia, malunion after fracture, internal fixation implants failure, and the residual deformities from previous osteotomy [ 3 5 ], which may cause unpredictable pathological and biomechanical changes of the proximal femur and femoral osteotomy. Therefore, total hip arthroplasty for femoral reconstruction and fixation are conventional treatment options used for patients without proximal femoral fractures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Однако в ряде случаев сложно добиться надежной первичной фиксации при использовании стандартных компонентов [109]. При деформациях бедренной кости, выраженной потере костной массы, некоторых врожденных сос тояниях, когда необходимо наряду с заменой сус тава выполнить реконструкцию проксимально-го отдела бедра, может возникнуть необходимость в раздельной подготовке метафиза и диафиза бед ра для установки ножки [110,111]. Модульные ножки предназначены для адекватного восстановления положения головки бедренной кости и достижения хорошего контакта метафизарной втулки с независимой фиксацией ножки в диафизе.…”
Section: модульный бедренный компонентunclassified